2017
DOI: 10.1016/j.jprot.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of daptomycin antibiotic against Staphylococcus aureus based on a quantitative bacterial proteome analysis

Abstract: DAP is a novel lipopeptide antibiotic that it exhibits excellent in vitro activity against most clinically relevant Gram-positive bacteria, and the investigations on its pharmaceutical action mode of DAP have dramatically increased in the past decade due to its unique antimicrobial mechanism. However, the target molecules of DAP acting on the infectious bacteria, are far from clear. The state-of-the-art quantitative proteomic technologies provide new avenues to uncover underlying mechanism of antibiotics. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…Despite this clear evidence that daptomycin does not directly inhibit peptidoglycan synthesis, studies continued to find cell wall-related phenotypes and stress response profiling showed induction of cell wall stress stimulons. Thus, daptomycin acts synergistically with beta-lactam antibiotics [89][90][91] and proteomic studies found induction of cell wall stress response proteins in both B. subtilis and S. aureus [54,66,92,93]. Likewise, cell wall stress stimulons were also found to be upregulated in transcriptomic datasets [43,92,94] and promotor activation studies [87,95].…”
Section: Is It Cell Wall Synthesis After All?mentioning
confidence: 94%
“…Despite this clear evidence that daptomycin does not directly inhibit peptidoglycan synthesis, studies continued to find cell wall-related phenotypes and stress response profiling showed induction of cell wall stress stimulons. Thus, daptomycin acts synergistically with beta-lactam antibiotics [89][90][91] and proteomic studies found induction of cell wall stress response proteins in both B. subtilis and S. aureus [54,66,92,93]. Likewise, cell wall stress stimulons were also found to be upregulated in transcriptomic datasets [43,92,94] and promotor activation studies [87,95].…”
Section: Is It Cell Wall Synthesis After All?mentioning
confidence: 94%
“…Presently, microbial proteomic technologies not only provide a powerful tool to profile protein expression in response to various stresses in a microorganism but also are used to reveal the possible mechanism of action of antibiotics (2527). For instance, comparative proteomic analyses revealed that bacillomycin L interacts with intracellular targets of Rhizoctonia solani hyphal cells and affects mitochondrial function, RNA processing and silencing, and calcium homeostasis (28).…”
Section: Introductionmentioning
confidence: 99%
“…NDK and NT5, two bacterial proteins sensitive to antibiotic daptomycin treatment [1], are marked with red dotted lines in metabolism pathway. Proteins interacting with NDK or NT5 are shown in green dotted line.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The data presented in this article are related to the research article entitled “Antibacterial mechanism of daptomycin antibiotic against Staphylococcus aureus based on a quantitative bacterial proteome analysis” (Ma et al, 2016) [1]. Nucleoside diphosphate kinase (NDK) and 5′-nucleotidase (NT5) are two proteins related to bacterial growth.…”
mentioning
confidence: 99%